UNRAVELING HAFAS FURQANI’S THOUGHT ABOUT THE METHODOLOGY OF ISLAMIC ECONOMICS - Ujang Syahrul Mubarrok; Muhamad Wahyudi; Izzani Ulfi (Univeristas Islam Bandung, 2021)
The methodology is important in developing Islamic economics. According to Hafas Furqani, the methodology is still general and has weaknesses, though several studies have classified it into several approaches. Therefore, this study aims to describe Hafas Furqani's thoughts regarding the methodology of Islamic economics in various journals. The method employed a literature review, primarily articles and books written by Hafas Furqani as well as another relevant sources. Subsequently, the results indicated that the development model of this methodology shows the process of preparing a structured economics building and birthing a theory derived from Islamic epistemology. Hafas Furqani stated that Islamic economics can become a new discipline, providing it has a clear subject matter, methodology to appraise theory, systematic accumulation of theory, and a well-organized body of knowledge.